Associations of muscle mass, strength, and quality with all-cause mortality in China: a population-based cohort study. Issue 11 (14th July 2022) - Wu, Man; Wei, Yuxia; Lv, Jun; Guo, Yu; Pei, Pei; Li, Jiachen; Du, Huaidong; Yang, Ling; Chen, Yiping; Sun, Xiaohui; Zhang, Hua; Chen, Junshi; et al.
Abstract: Background: It remains unclear about the association of muscle mass, strength, and quality with death in the general Chinese population of diverse economical and geographical backgrounds. The present study aimed to comprehensively examine such associations across different regions in China. Methods: Based on the China Kadoorie Biobank study, the present study included 23, 290 participants who were aged 38 to 88 years and had no prevalent cardiovascular diseases or cancer. Muscle mass and grip strength were measured using calibrated instruments. Arm muscle quality was defined as the ratio of grip strength to arm muscle mass. Low muscle mass, grip strength, and arm muscle quality were defined as the sex-specific lowest quintiles of muscle mass index, grip strength, and arm muscle quality, respectively. Cox proportional hazards models yielded hazard ratios (HRs) and 95% confidence intervals (CIs) for risks of all-cause mortality in relation to muscle mass, strength, and quality. Results: During a median follow-up of 3.98 years, 739 participants died. The HR (95% CI) of all-cause mortality risk was 1.28 (1.08–1.51) for low appendicular muscle mass index, 1.38 (1.16–1.62) for low total muscle mass index, 1.68 (1.41–2.00) for low grip strength, and 1.41 (1.20–1.66) for low arm muscle quality in models adjusted for sociodemographic characteristics, lifestyle factors, and medical histories. Conclusion: Low muscle mass, grip strength, and arm muscle quality are all associated with short-term increased risks of mortality, indicating the importance of maintaining normal muscle mass, strength, and quality for general Chinese adults.